2013
DOI: 10.1620/tjem.231.117
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Link between Heme Oxygenase and the Signaling Pathway of DNA Damage in<i> Drosophila</i> <i>Melanogaster</i>

Abstract: Heme oxygenase (HO) is a rate-limiting step of heme degradation, which catalyzes the conversion of heme into biliverdin, iron, and CO. HO has been characterized in microorganisms, insects, plants, and mammals. The mammalian enzyme participates in adaptive and protective responses to oxidative stress and various inflammatory stimuli. The present study reports that eye imaginal disc-specific knockdown of the Drosophila HO homologue (dHO) conferred serious abnormal eye morphology in adults, resulting in the gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 41 publications
0
14
0
Order By: Relevance
“…Ida et al ( 2013 ) also observed a significant drop in proliferating cells and an increase of DNA damage detected in the eye imaginal disks of the larva after treatment with HO dsRNA. Ida et al ( 2013 ) performed a genomic screen leading to the identification of eight genomic regions that suppressed the observed rough eye phenotype during HO knockdown. This indicates that specific genes on these isolated regions may interact with HO and help counteract its loss during a knockdown event, however further work is needed to isolate specific genes.…”
Section: Heme Catabolismmentioning
confidence: 88%
See 2 more Smart Citations
“…Ida et al ( 2013 ) also observed a significant drop in proliferating cells and an increase of DNA damage detected in the eye imaginal disks of the larva after treatment with HO dsRNA. Ida et al ( 2013 ) performed a genomic screen leading to the identification of eight genomic regions that suppressed the observed rough eye phenotype during HO knockdown. This indicates that specific genes on these isolated regions may interact with HO and help counteract its loss during a knockdown event, however further work is needed to isolate specific genes.…”
Section: Heme Catabolismmentioning
confidence: 88%
“…Immunostaining the eye tissue of HO knockdown larvae revealed high concentrations of activated caspase-3, an apoptotic marker, as well as larger than normal iron deposits, both of which were thought to contribute to the rough eye phenotype observed. This observed phenotype was later linked to G1/S arrest of the cell cycle leading to cell death due to increased generation of reactive oxygen species (Ida et al, 2013 ). Ida et al ( 2013 ) also observed a significant drop in proliferating cells and an increase of DNA damage detected in the eye imaginal disks of the larva after treatment with HO dsRNA.…”
Section: Heme Catabolismmentioning
confidence: 99%
See 1 more Smart Citation
“…Although they differ in distribution and functions, they both act as cytoprotective and anti-apoptotic agents in an organism, by scavenging reactive oxygen species (ROS; reviewed in [1]). In Drosophila melanogaster , there is only one gene encoding HO [2] that plays an important role in development [3] and in controlling the signaling pathway of DNA damage [4]. Any other functions of HO in insects are still unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In mammals, two HO proteins, inducible HO-1 and constitutive HO-2, are encoded by two different genes and have cytoprotective and anti-apoptotic functions by scavenging reactive oxygen species (ROS) 1 . Drosophila has only one gene encoding HO 2 that plays an important role in development 3 and in controlling the DNA damage signalling pathway 4 .…”
Section: Introductionmentioning
confidence: 99%